The Comparison of Islamic Governance Disclosure Practices in Indonesian Sharia Banks - Ahmad Nurkhin; Agus Wahyudin; Fachrurrozie Fachrurrozie; Anna Kania Widiatami; Puji Novita Sari (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
Islamic banks in Indonesia (Bank Syariah Mandiri, BNI Syariah dan BRI Syariah) have merged in 2021 to become Bank Syariah Indonesai (BSI). This study aims to compare the practice of Islamic Governance Disclosure (IGD) of Idonesian Islamic banks before the merger period. A descriptive quantitative research approach was used in this research. The sampling method used was purposive sampling with the criteria of three Islamic banks that carried out a merger in 2021. Islamic banks which were the samples of this study were Bank Syariah Mandiri, BRI Syariah and BNI Syariah. The observation period is 5 years (2014-2018). The documentation method is used for data retrieval using the check list tool. Content analysis method is used to analyze the data that has been obtained. This method is used to determine the IGD index which consists of three main indices, namely the Sharia Supervisory Board (DPS) disclosure index, the DPS report disclosure index, and the zakat disclosure index. The results showed that the three Islamic banks had a fairly good IGD index for 3 years. Bank Syariah Mandiri and BNI Syariah show the highest and most consistent IGD index for five consecutive years compared to BRI Syariah. The IGD Index for Bank Syariah Mandiri and BNI Syariah are the same in 2015-2017. The IGD index of BRI Syariah has fluctuated over the past five years.